Antioxidant Activity of Placenta Extracts After Low Temperature and Hypothermic Storage - Rozanova, S. L.; Rozanova, E. D.; Nardid, O. A.; Karpenko, V. G. (Problems of Cryobiology and Cryomedicine, 2024)
The experimental data, obtained under comparative evaluation of hypothermic and low temperature storage influence on human placenta extract (HPE) antioxidant activity have been presented. Antioxidant activity was assessed by capacity to reduce the ferric iron and ABTS+ radical, to chelate ferrous ions and by phenolic compound content. Twelve-month low temperature storage both in liquid nitrogen (–196°С) as well as in freezing chamber (–20°С) has been shown to preserve HPE antioxidant activity at a high level while during hypothermic storage (4°С) such an activity keeps up to 7 days.